Sosialisasi Peningkatan Konsumen Bahan Pangan Organik Dan Kewaspadaan Terhadap Jajanan Yang Tidak Sehat Di SMPN 17 Kota Bengkulu - Saputra, Irem; Zaky Apriadi; Alhakim, Muhammad Farid; Juni Afriansyah; Kanata, Refal Yoriko; Moulina, Methatias Ayu; Hesti Nur’aini; herri Fariadi (Utami Publisher, 2025)
SMP NEGERI 17 BENGKULU CITY is one of the junior high schools with state status located in the district. Muara Bangkahulu, Bengkulu City,. SMP N 17 Bengkulu City was founded on April 1 1993 with Establishment Decree Number 0313/0/1993 which is under the auspices of the Ministry of Education and Culture. In learning activities, this school which has 622 students is guided by 40 teachers who are professionals in their fields. Students from SMPN 17 Bengkulu City are being prepared to become skilled workers in increasing consumers of organic food and awareness of unhealthy snacks. To support the vision of the junior high school in equipping its students with awareness of the dangers of unhealthy snacks, socialization was carried out to increase consumers of organic food and awareness of unhealthy snacks. The aim of this outreach is, among other things, to provide additional knowledge regarding increasing consumers of organic food and awareness of unhealthy snacks. This activity was carried out using a seminar and question and answer method which was enthusiastically welcomed by the school. The results of this activity were able to increase the knowledge of students at SMPN 17 Bengkulu City regarding increasing consumers of organic food and awareness of unhealthy snacks.